Red/Orange Autofluorescence in Selected Candida Strains Exposed to 405 nm Laser Light - Rafał Wiench; Dariusz Paliga; Anna Mertas; Elżbieta Bobela; Anna Kuśka-Kiełbratowska; Sonia Bordin-Aykroyd; Aleksandra Kawczyk-Krupka; Kinga Grzech-Leśniak; Monika Lukomska-Szymanska; Edward Lynch; Dariusz Skaba (MDPI AG, 2024)
Background: Candida albicans and similar species are significant pathogens in immunocompromised and hospitalized individuals, known for mucosal colonization and bloodstream/organ invasion. Many pathogenic fungi, including these species, exhibit autofluorescence (R/OF) under specific light conditions, a feature crucial for their detection. Aim: We investigated the use of a 405 nm diode laser for the direct observation of red/orange autofluorescence of Candida spp., common in the oral cavity, exploring its potential in health screenings. Methods: This study utilized cultures of Candida spp. on Sabouraud dextrose agar with Qdot 655 and 685 for fluorescence benchmarking, illuminated using a 405 nm diode laser (continuous wave, power 250 mW, 0.0425 J/cm² fluence, 0.0014 W/cm² power density). Images were captured using a yellow-filter camera at set intervals (48 to 144 h). Visual and computational analyses evaluated the R/OF in terms of presence, intensity, coloration, and intra-colony variation. Results: Most Candida strains displayed red/orange autofluorescence at all observation times, characterized by varied coloration and intra-colony distribution. Initially, there was an increase in R/OF intensity, which then stabilized in the later stages of observation. Conclusions: The majority of the Candida strains tested are capable of emitting R/OF under 405 nm laser light. This finding opens up new possibilities for integrating R/OF detection into routine dental screenings for Candida spp.